2010
DOI: 10.1016/j.paid.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional functioning and face recognition ability in the normal population

Abstract: Recent research indicates face recognition ability varies within the normal population. To date, two factors have been identified that influence this cognitive process: the age and gender of the perceiver. In this paper, we examine the influence of socio-emotional functioning on face recognition ability. We invited participants with high and low levels of empathy (as indicated by the Empathy Quotient) to take part in a face recognition test. Participants were asked to study a set of faces, and at test viewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 29 publications
1
41
2
1
Order By: Relevance
“…It has been reported in behavioral and imaging studies that higher self-reported empathy (as assessed by scores in questionnaires) may be associated to various degrees with higher performance accuracy and/or higher activation of brain regions implicated in action understanding, theory of mind, and emotional processing. This has been observed in a number of tasks and situations, such as face recognition (Bate, Parris, Haslam, & Kay, 2010), perception of emotional expressions and actions (Decety & Chaminade, 2003;Pfeifer, Iacoboni, Mazziotta, & Dapretto, 2008;Schulte-Rüther, Markowitsch, Fink, & Piefke, 2007;Zaki, Bolger, & Ochsner, 2008, pain perception (Lamm, Batson, & Decety, 2007;Singer, Seymour, O'Doherty, Stephan, Dolan, & Frith, 2004), action perception (Gazzola, Aziz-Zadeh, & Keysers, 2006;Kaplan & Iacoboni, 2006), engaging in mimicry (Chartrand &Bargh, 1999), andPsychological Research (2011) 75:423-434 425 disposition towards prosocial behavior (Davis, Mitchell, Hall, Lothert, Snapp, & Meyer, 1999;Eisenberg & Miller, 1987;Greitemeyer 2009). Based on this previous research, we hypothesized that empathy indices may have a positive relation to performance in the recognition tasks.…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported in behavioral and imaging studies that higher self-reported empathy (as assessed by scores in questionnaires) may be associated to various degrees with higher performance accuracy and/or higher activation of brain regions implicated in action understanding, theory of mind, and emotional processing. This has been observed in a number of tasks and situations, such as face recognition (Bate, Parris, Haslam, & Kay, 2010), perception of emotional expressions and actions (Decety & Chaminade, 2003;Pfeifer, Iacoboni, Mazziotta, & Dapretto, 2008;Schulte-Rüther, Markowitsch, Fink, & Piefke, 2007;Zaki, Bolger, & Ochsner, 2008, pain perception (Lamm, Batson, & Decety, 2007;Singer, Seymour, O'Doherty, Stephan, Dolan, & Frith, 2004), action perception (Gazzola, Aziz-Zadeh, & Keysers, 2006;Kaplan & Iacoboni, 2006), engaging in mimicry (Chartrand &Bargh, 1999), andPsychological Research (2011) 75:423-434 425 disposition towards prosocial behavior (Davis, Mitchell, Hall, Lothert, Snapp, & Meyer, 1999;Eisenberg & Miller, 1987;Greitemeyer 2009). Based on this previous research, we hypothesized that empathy indices may have a positive relation to performance in the recognition tasks.…”
Section: Introductionmentioning
confidence: 93%
“…Although Bowles et al (2009) make the case that their participants who were candidates for DP also performed very poorly on a famous face test, it is not clear whether at least some people who are thought to have DP are simply those at the "bottom end of normal". Evidence supporting this perspective comes from findings that the face-recognition continuum is broader than originally thought, with substantial variation in performance within the typical population (e.g., Bate, Parris, Haslam, & Kay, 2010;Wang, Li, Fang, Tian, & Liu, 2012). Furthermore, some work has identified individuals at the opposite extreme to those with DP-so-called "super-recognizers", who have extraordinarily good face-recognition skills (e.g., Bobak, Bennetts, Parris, Jansari, & Bate, 2016;Bobak, Dowsett, & Bate, 2016;Bobak, Hancock, & Bate, 2016;Russell, Duchaine, & Nakayama, 2009).…”
Section: Developmental Prosopagnosia: Historical Backgroundmentioning
confidence: 99%
“…Apart from extreme cases of individuals with prosopagnosia who are unable to recognize individuals by their faces (see Ellis & Florence, 1990 for an English translation of Bodamer's original description from 1947) and 'super-recognizers' who are reported to never forget a face (Russell, Chatterjee, & Nakayama, 2012), large differences in face recognition skills in the normal population have also begun to attract scientific interest (e.g., Bindemann et al, 2012). Investigating such individual differences can promote better understanding of normal face identity processing (see also Yovel, Wilmer, & Duchaine, 2014), and recent years have seen an increasing number of relevant published papers (e.g., Attwood, Penton-Voak, Burton, & Munafo, 2013;Bate, Parris, Haslam, & Kay, 2010;Susilo, Germine, & Duchaine, 2013). Here, we specifically focused on individual differences in face-specific identity-processing skills and their relationship to the individual utilization of shape versus texture information.…”
mentioning
confidence: 99%